The burden and clinical manifestation of hospitalized influenza among different pediatric age-groups in the tropics - Chong, Chia Yin (2020)
Introduction: In tropical Singapore, influenza occurs all year‐round. This study of influenza‐confirmed hospitalized pediatric patients compared clinical characteristics and complications by age‐group and differences between influenza A and B. Methods: This was a retrospective study of pediatric inpatients from January 2013 to December 2014. Patients were grouped into: <6 months, 6 months to <5 years, 5‐ to <10‐year and ≥10 years. Complications were classified into neurologic, pulmonary, and other. We also calculated the incidence of hospitalized influenza cases per 100 000 age‐related population. Results: There were a total of 1272 patients with a median age of 37 months. The highest hospitalization rates were in the <6 months age‐group. Majority (75.2%) had no comorbidity; 25.6% had complications: neurologic 11.9%, pulmonary 9.6%, other 4.1%. Patients with other complications were older, male, and had the highest influenza B rates and the longest length of stay. Influenza A comprised 76.9% of cases and had higher complication rates especially neurologic, compared to influenza B. Influenza B patients were older and were more likely to develop other complications. The 6‐month to <5‐year‐age‐group had the highest complication rate (30.6%), especially neurologic. However, ≥10 years old had the highest other complications, ICU/ high‐dependency admissions and influenza B Victoria rates. Conclusions: Infants <6 months had the highest hospitalization rates for influenza. The 6‐month to <5‐year‐age‐group had the highest complication rate especially neurologic. Influenza A patients were younger, had higher seizure rates and complications compared to influenza B.